INCONSISTENCY OF THE UTERINE SCAR, MODERN APPROACHES TO CORRECTION - Щедрина, Ирина Дмитриевна; Малушко, Антон Викторович; Фаткуллина, Ирина Борисовна; Алексеев, Сергей Михайлович; Махинов, Владимир Алексеевич (Mother and Baby in Kuzbass, 2025)
Uterine scar failure after cesarean section is a pressing problem in modern gynecology with an incidence rate of 35% to 88% depending on the number of previous surgeries. This pathology is characterized by the formation of a defect in the scar area and can lead to menstrual irregularities, reproductive problems, and complications in subsequent pregnancies.The paper presents a systematic review of modern approaches to the diagnosis and correction of uterine scar failure based on an analysis of scientific literature from the PubMed/MEDLINE, Cochrane Library, eLibrary.ru, and other databases.Pathogenetic mechanisms of defective scar formation are considered, including two types of regeneration – substitution and restitution. The article analyzes diagnostic methods using transvaginal echography as the gold standard, magnetic resonance imaging, and hysteroscopy. Modern correction methods are presented, including conservative therapy, hysteroscopic interventions using robotic systems, laparoscopic correction with both scar tissue excision and an innovative approach without scar resection.Particular attention is paid to robotic surgery using the da Vinci system, which has demonstrated high efficiency with an increase in the thickness of the myometrium to 9.25 mm and the absence of relapses. Promising areas of regenerative medicine are considered, including the use of platelet-rich plasma and tissue engineering methods with biodegradable scaffolds.The need for a personalized approach to choosing a correction method is emphasized, taking into account the size of the defect, clinical manifestations, and the patient's reproductive plans.
Keywords: uterine scar failure; isthmocele; cesarean section; laparoscopic correction; hysteroscopic treatment; robotic surgery